P250 Barium vs endoscopy for diagnosis of UGI cancer, stratified by Edinburgh dysphagia score during COVID-19. (19th June 2022) - Chambers, Thomas; Abdelatie, Ahmed; Turner, Karen; Dhar, Anjan
Abstract : Introduction: During the first wave of Covid-19 pandemic, Public Health England and the British Society of Gastroenterology paused elective 2 week wait Upper GI endoscopy services as part of the strategy of minimising risk of virus transmission, as it is an aerosol generating procedure. Consequently, this led to a huge backlog of deferred and delayed endoscopies and a long list of catch up endoscopies. County Durham adopted a strategy of combing barium swallow & meal and endoscopy as a means of managing this workload. Aim of this study: To analyse the outcomes of a combined barium swallow and meal vs upper GI endoscopy for the diagnosis of cancer using a retrospective Edinburgh Dysphagia Score (EDS) stratification. Patients who were referred with dysphagia under 2 week wait were divided, at the discretion of the triage clinician, into two groups: one group was offered barium swallow & meal and the second group triaged to endoscopy as their first investigation. EDS was not calculated at the point of triage since the 2 week referral did not have all the details for doing this. Methods: 380 patients were included in this study between 1 st July 2020 and 30 th June 2021. 76 patients had barium study only, while 290 patients had solely endoscopy. 14 patients underwent testing with both modalities. Clinical data to calculate a retrospective EDS was collected from the Electronic patient record, and results of investigations from a Clinical Manager System (iSoft®). The EDS divided as ≥ 3.5 (high risk for cancer) and < 3.5 (low risk) patients. Results were then analysed using Microsoft Excel®. Results: 28 patients were found to have cancer (crude incidence 7.3%); M:F=1.8, mean age 75.2 years. Only 2 cancers were diagnosed by barium (2.22%), whereas 26 (8.55%) were detected by endoscopy. 1 patient with a suspicion of cancer at barium (EDS 4) was confirmed at endoscopy. Mean EDS for all pts with cancer 7.46 (both pts in the barium group had EDS ≥ 3.5 and none of the pts in the endoscopy group with EDS < 3.5 had cancer). Mean EDS for patients with cancer in the Barium group was 5.5 and in the endoscopy group was 7.2. Overall, the EDS for non-cancer patients was also greater than 3.5 (mean = 4.36). The two cancers in the barium group were adenocarcinomas at the OG junction. Distribution of cancers in the endoscopy group: 7 OG junction cancers, 12 were distal/lower oesophageal (9 adenocarcinoma, 1 squamous cell carcinoma (SCC) and 2 undifferentiated), 4 were mid/upper oesophagus (all SCC) and 3 were gastric cancers (2 adenocarcinoma and 1 GIST). 6 patients were found to have early-stage cancer (1 in barium and 5 in endoscopy group), whereas 20 were advanced stage cancers (1 in barium and 19 in endoscopy group). Conclusion: Despite EDS scores being >3.5, the upper GI cancer pick up rate among barium swallow patients is low, at 2.22%, whereas cancer pick up rate among endoscopy patients was higher at 8.55%, clearly indicating that endoscopy is more sensitive in detecting upper GI cancers than barium studies. Cancer patients have high EDS with an average score of 7.46 compared to non-cancer patients. None of the cancer pts had a low EDS (≤3.5), validating the clinical utility of the EDS as a triage tool to stratify pts with dysphagia into low and high-risk groups for investigation by barium or endoscopy, respectively.